PENGEMBANGAN MODUL GAMBAR TEKNIK DAN AUTOCAD DALAM PEMBELAJARAN GAMBAR TEKNIK SISWA KELAS X TKR DI SMK NEGERI 3 YOGYAKARTA - Alwidiantoro; Sukaswanto (Journal of Automotive Technology and Education, 2024)
The research aims to: (1) make technical drawing modules and AutoCAD basics tath can help students learn during the COVID-19 pandemic, (2) Determine the feasibility of the engineering drawing module and the basics of AutoCAD to be used as student learning materials in the engineering drawing subject of class X majoring in Light Vehicle Engineering at SMK N 3 Yogyakarta (2) Knowing the effectiveness of the modules developed to support learning subjects engineering drawing lessons class X majoring in Light Vehicle Engineering SMK N 3 Yogyakarta. This research was conducted by using the method of the research and development (RnD). The research Model used referring to a flow step of the development of Borg & Gall. n this study, we will use development based on the development steps of Borg & Gall; (1) the Collection of initial information, (2) Planning, (3) Development of the initial module, (4) limited Testing and product revision, and (5) Testing and revision of the product. Research data collection was carried out using questionnaires and observations. In this study, researchers will use an instrument in the form of a questionnaire to obtain data. The results of this study are: (1) media in the from of technical drawing modules and AutoCAD basics that can help students learn during the COVID-19 pandemic, (2) assessment of the feasibility level of the learning module includes aspects of media, materials, small trials, and large trials. The feasibility of the module in terms of the results of the expert validation of the module media got "very feasible" results. Based on the feasibility of the module in terms of the results of the material expert validation, the results were "very feasible". Based on student responses, the media module got "wort it" results. (3) The developed media is declared effective with indicators of increasing student learning outcomes before using the module media and after using the module media.